Assessment of liver slices for research on metabolic drug–drug interactions in cattle - Viviani, Paula (2017)
1. Precision-cut liver slices (PCLS) from food-producing animals have not been extensively used to study xenobiotic metabolism, and thus information on this field of research is sparse.2. The aims of the present work were to further validate the technique of production and culture of bovine PCLS and to characterize the metabolic interaction between the anthelmintic albendazole (ABZ) and the flavin-monooxygenase (FMO) inhibitor methimazole (MTZ).3. Nine steers were used as donors. PCLS were produced and incubated under two methods: a dynamic organ culture (DOC) incubator and a well-plate (WP) system.4. Tissue viability, assessed through both structural and functional markers, was preserved throughout 12 h of incubation. ABZ was metabolized to its (+) and (-) albendazole sulfoxide stereoisomers (ABZSO) in bovine PCLS. The interaction between ABZ and MTZ resulted in a reduction (p < 0.001) in the rates of appearance of (+) ABZSO. Conversely, in presence of MTZ, the rates of appearance of (−) ABZSO increased under both systems (p < 0.05).5. Both culture systems were suitable for assessing the interaction between ABZ and MTZ.6. Overall, the results presented herein show that PCLS are a useful and reliable tool for short-term studies on metabolic drug?drug interactions in the bovine species.